2022
DOI: 10.1038/s41598-022-11995-y
|View full text |Cite
|
Sign up to set email alerts
|

6-Bromo-2-naphthol from Silene armeria extract sensitizes Acinetobacter baumannii strains to polymyxin

Abstract: The overuse of antibiotics has led to the emergence of multidrug-resistant bacteria, which are resistant to various antibiotics. Combination therapies using natural compounds with antibiotics have been found to have synergistic effects against several pathogens. Synergistic natural compounds can potentiate the effects of polymyxins for the treatment of Acinetobacter baumannii infection. Out of 120 types of plant extracts, only Silene armeria extract (SAE) showed a synergistic effect with polymyxin B (PMB) in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Individual deletions in all three MTase genes ( aamA , dcmA and dcmB ) were performed using the CRISPR/Cas9-based system through which a 200 bp fragment (starting from the first adenine nucleotide located between nucleotides 216–224) was successfully removed; in the case of the aamA gene, the cofactor binding FXGXG motif was completely deleted (see Methods) (). Loss of AamA led to slower growth in aamA mutant ([8.0±0.2] / [ h ×100], P< 0.05) compared to WT ([11.2±0.0] / [ h ×100]) in LB (5 ml), but no significant growth defects were observed in other dcm mutants () [47–49]. When growth media and conditions (aeration, pH) were changed to monitor the growth behaviour of each strain including the complementation strain ( ∆aamA /pRK415:: aamA ) and the vector controls (ATCC 17978/pRK415, ∆aamA /pRK415), the growth retardation of the aamA mutant remained the same under all test conditions except for the R2A (2 x) broth media, and the aamA complemented strain failed to restore the growth rate ( and S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual deletions in all three MTase genes ( aamA , dcmA and dcmB ) were performed using the CRISPR/Cas9-based system through which a 200 bp fragment (starting from the first adenine nucleotide located between nucleotides 216–224) was successfully removed; in the case of the aamA gene, the cofactor binding FXGXG motif was completely deleted (see Methods) (). Loss of AamA led to slower growth in aamA mutant ([8.0±0.2] / [ h ×100], P< 0.05) compared to WT ([11.2±0.0] / [ h ×100]) in LB (5 ml), but no significant growth defects were observed in other dcm mutants () [47–49]. When growth media and conditions (aeration, pH) were changed to monitor the growth behaviour of each strain including the complementation strain ( ∆aamA /pRK415:: aamA ) and the vector controls (ATCC 17978/pRK415, ∆aamA /pRK415), the growth retardation of the aamA mutant remained the same under all test conditions except for the R2A (2 x) broth media, and the aamA complemented strain failed to restore the growth rate ( and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of AamA led to slower growth in aamA mutant ([8.0±0.2] / [h×100], P<0.05) compared to WT ([11.2±0.0] / [h×100]) in LB (5 ml), but no significant growth defects were observed in other dcm mutants (Fig. 1b) [47][48][49]. When growth media and conditions (aeration, pH) were changed to monitor the growth behaviour of each strain including the complementation strain (∆aamA/pRK415::aamA) and the vector controls (ATCC 17978/pRK415, ∆aamA/pRK415), the growth retardation of the aamA mutant remained the same under all test conditions except for the R2A (2 x) broth media, and the aamA complemented strain failed to restore the growth rate (Figs 1c and S2).…”
Section: Identification and Deletion Analyses Of Three Putative Mtase...mentioning
confidence: 97%
“…By comparing changes in metabolites and metabolic pathways, they found that after PMB disrupted the bacterial outer membrane, rifampicin entered the intracellular space to inhibit DNA and RNA synthesis, which led to the synergistic activity of PMB with rifampicin [ 31 ]. A variety of mechanisms are proposed to mediate PMB synergism, including increased membrane perturbations, LPS modifications, the use of efflux pumps, the formation of capsules, and the overexpression of the outer membrane protein OprH [ 32 , 67 , 68 ]. In our study, using metabolomic analysis, we found that SA enhanced the membrane perturbations caused by PMB, consistent with the pharmacological results of the synergistic activity of PMB-SA in membrane disruption.…”
Section: Discussionmentioning
confidence: 99%